Kernel technologies and applications of AVS2 video coding standard - Siwei MA; Falei LUO; Tiejun HUANG (Dianxin kexue)
A brief introduction was given to the development history of AVS video coding standards.Then an overview of the key technologies adopted in AVS2 video coding standard (GB/T 33475.2-2016) was provided,including flexible prediction partition,multiple hypothesis prediction,optimized two-level transform,adaptive loop filter and background picture model based prediction coding for scene video.Compared to the AVS1,AVS2 can achieve more than 50% bits saving.And compared to HEVC/H.265,AVS2 can achieve significant coding efficiency improvement for scene video coding.Moreover,the applications of AVS standard in digital TV broadcasting was introduced briefly.